2020
DOI: 10.1371/journal.pone.0232151
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal colonization prevalence and density among Thai children with severe pneumonia and community controls

Abstract: Background Pneumococcal colonization prevalence and colonization density, which has been associated with invasive disease, can offer insight into local pneumococcal ecology and help inform vaccine policy discussions. Methods The Pneumonia Etiology Research for Child Health Project (PERCH), a multi-country casecontrol study, evaluated the etiology of hospitalized cases of severe and very severe pneumonia among children aged 1-59 months. The PERCH Thailand site enrolled children during January 2012-February 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…We expect a positive correlation between observed CT values and bacterial burden, and between bacterial burden and the presence and intensity of symptoms. Indeed, such a relationship has been shown for Streptococcus pneumoniae , where NP carriage density was much higher in children with pneumococcal pneumonia compared with asymptomatic carriers ( Piralam et al, 2020 ; Deloria Knoll et al, 2017 ). As defined, our EFI uses each subject’s full set of NP samples to provide an aggregate measure of the evidence for pertussis infection in that subject, and incorporates information regarding both the number of detecting assays and the CT values for each result.…”
Section: Resultsmentioning
confidence: 75%
“…We expect a positive correlation between observed CT values and bacterial burden, and between bacterial burden and the presence and intensity of symptoms. Indeed, such a relationship has been shown for Streptococcus pneumoniae , where NP carriage density was much higher in children with pneumococcal pneumonia compared with asymptomatic carriers ( Piralam et al, 2020 ; Deloria Knoll et al, 2017 ). As defined, our EFI uses each subject’s full set of NP samples to provide an aggregate measure of the evidence for pertussis infection in that subject, and incorporates information regarding both the number of detecting assays and the CT values for each result.…”
Section: Resultsmentioning
confidence: 75%
“…To understand the role of pneumococcal colonisation in ALRI in children from Myanmar, we also evaluated the nasopharyngeal colonisation rates using PCR and found a high positive rate (up to 45%) in the nasopharynx. Previous studies evaluating the pneumococcal nasopharyngeal colonisation have shown similar rates, with 54.5% and 62.5% in children aged 2-59 months in India (83) and aged 1-59 months in Thailand (84), respectively. Our results demonstrated that pneumococcal colonisation was common in children from Myanmar, providing the baseline colonisation rate in the early stages of the 10-valent PCV's introduction.…”
Section: Discussionmentioning
confidence: 56%
“…Another study of children aged <5 years and hospitalized with pneumonia found carriage rates of 27%, whereas outpatients with influenza-like illness had a carriage rate of 60% (Levine et al, 2006). A more recent study of children aged <5 years found that the prevalence of nasopharyngeal colonization did not differ significantly between individuals with severe/very severe pneumonia and community controls (54.5% vs 62.5%, respectively; P = 0.12) (Piralam et al, 2020). It should be noted that the methods used for detecting S. pneumoniae varied among the studies considered in the present review (Lee et al, 2001;Moisi et al, 2016;Thummeepak et al, 2015;Turner et al, 2012;Levine et al, 2006;Piralam et al, 2020), and these methodological differences could have contributed to the differences in the observed carriage rates.…”
Section: Nasopharyngeal Carriagementioning
confidence: 95%
“…A study of children aged <5 years during 2006 showed that 55% of carriage isolates included PCV7 serotypes (Levine et al, 2006). More recently, a study conducted during 2012-2014 found a high percentage of nasopharyngeal isolates from children aged <5 years with severe/very severe pneumonia and community controls contained serotypes included in PCV10/PHiD-CV (70.0% and 61.8%, respectively) and PCV13 (76.7% and 67.9%) (Piralam et al, 2020). Further studies are required to obtain a more complete overview of the pneumococcal serotypes contained in carriage isolates.…”
Section: Serotyping Surveillancementioning
confidence: 99%
See 1 more Smart Citation